Gender-based violence is a blind spot for sports and exercise medicine professionals - Wheatley, L.; McKeon, G.; Pebole, M.; Wells, R.; Rees, S.; Ward, P. B.; Rosenbaum, S. (Sports Medicine, 2023)
The American Medical Society for Sports Medicine (AMSSM) Position Statement on sexual violence (SV) in sports has identified SV as a serious public health and societal issue that has long-standing negative impacts on athletes` physical and mental wellbeing [1]. The position statement highlighted the important role healthcare providers can play in identifying and responding to the health impacts of sexual violence. A 2021 `patient voices article` challenges clinicians in the sports and exercise medicine (SEM) community to do better when asking about and responding to athlete disclosures of SV [2]. This is significant for SEM professionals working with athletes of all levels, as well as treating the general population engaging in exercise for health and rehabilitation.